Physiological Implications of Broiler Chickens Diet Fortified with Tiger Nuts (Cyperus esculentus) - Ilo, S.U.; Ugwu, O.A.; Ogba, C.U.; Ogbu , O.C. (International Journal of Poultry Science, 2020)
Background and Objective: The quest to ameliorate protein food shortages have continuously made researchers to seek alternative sources of feed stuff that will be cheaper and less competitive with man. Tiger-nut is the richest tuber in terms of protein. It is rich in vitamins and minerals. Using it in the diet of broiler birds in two growth phases (starter and finisher) promoted growth. This study was conducted to investigate the effect of tiger nut on the growth performance of broiler chicken. Materials and Methods: A total of eighty four broilers were used for the study. The birds were randomly assigned to four treatment groups with a total of 21 birds per treatment. The treatments were T1 (0%) T2 (5%) T3 (10%) and T4 (15%). T1 served as the control. The treatments were replicated 3 times with 7 broiler birds per replicate. Results: Weight gain was significantly (p<0.05) higher among the tiger-nut fortified groups, with T3 (5520 g) gaining the highest weight. Feed intake increased significantly (p<0.05) with increase in the quantity of tiger nuts. Feed efficiency was lower among the tiger nut fortified groups with T2 (2.98) diet having the most efficient diet. Weight of prime cut parts like the back cut, breast muscle and paired wings were significantly higher among the tiger-nut fortified groups when compared with the control. The mean cell haemoglobin (MCH), mean cell volume (MCV) and white blood cells differed significantly among the treatment group in both the starter and finisher stage. Conclusion: The study showed that there were improvement in the growth rate of broilers fed tiger nut, this was witnessed in the weight of cut part of the broiler birds. The haematology was not affected by tiger-nut fortification. Therefore, increase in body weight gain and best feed efficiency was observed in T2 (5%) that was the best level for maize replacement with tiger nuts.